A review of the good practices of active mobility measures implemented by European cities due to the COVID-19 pandemic. Issue 1 (November 2021) - Nalmpantis, Dimitrios; Vatavali, Fereniki; Kehagia, Fotini
Abstract: The scope of this paper is to make a review of the good practices of active mobility measures implemented by big European cities to face the changing travel patterns and the social distancing requirement due to the COVID-19 pandemic. Active mobility good practices were gathered by 50 postgraduate students and they were categorized by the authors. 50 European cities were reported, of which four (4) were examined further as the most reported ones. These were the following: Paris, France; Milan, Italy; Brussels, Belgium; and Berlin, Germany. This does not mean that these cities are the best performing in active mobility, as there could be cities that already had adequate active mobility performance, and other factors interfere, such as the brand name of each city. The most reported good practice was the temporary pop-up bicycle lanes, also applied in Thessaloniki, Greece. Another good practice is the expansion of pedestrianization and the speed limit of 30 km/h. Athens, Thessaloniki, and other Greek cities have a lot to learn from the experience of the other European cities, and this paper is an attempt of knowledge transfer. It seems that the crisis of the COVID-19 pandemic has become an excellent opportunity for the promotion of active mobility in Europe that should not be left unexploited.